Fundamentals of fluvial geomorphology [electronic resource] - Charlton, Ro (Routledge, 2008)
Fundamentals of Fluvial Geomorphology' is an introductory text for first and second year undergraduates, providing a clear understanding of how the fluvial system operates at different spatial and temporal scales